Erosion Wear and Hardness of Glass Fiber / Epoxy with Nano and Micro TiO2 Hybride Composites - Al-Zubaidi, Aseel Basim; Al-Tabbakh, Ahmed A; Ahmed, Shatha Riyad; Achour, Amine (Al-Nahrain Journal of Science, 2018)
The objective of this research is to prepare and study (Glass Fiber / Epoxy) with nano and micro Titanium dioxide (TiO2) composites with different volume percentage of nano and micro TiO2 powder of 2%, 4%, and 6% volume fraction. Atomic force microscopy techniques was used to measure the grain size of nano TiO2 powder (average diameter was 46 nm) and particle size analyzer techniques was used. Erosive wear behavior of this composite under three different impingement angles of 30°, 60° and 90° and three angular silica sand abrasive particle sizes approximately 425, 600 and 850 μm and hardness (shore D) were studied. In general the erosion wear of micro composites have lower erosion resistance than other nano-based compounds. Erosion resistance increase as the volume fraction increase. Nano composites of GF / EP with TiO2 have many advantages over micro composites from the view point of wear and hardness tests. The worn surface features of unfilled and filled G-E composites were examined using scanning electron microscopy (SEM) and results indicates more severe damage to matrix and glass fiber in unfilled composite system as compared to TiO2 filled composites.